2023
DOI: 10.1097/inf.0000000000004096
|View full text |Cite
|
Sign up to set email alerts
|

Pooling Saliva Sample as an Effective Strategy for the Systematic CMV Screening of Newborns—A Multicentric Prospective Study

Maria-Jesus Chasqueira,
Catarina Fernandez,
Augusta Marques
et al.

Abstract: Background: Cytomegalovirus is the most common cause of congenital infections worldwide. Screening all newborns in the first 2 weeks of life is the only way to detect all cases of congenital infection, allowing the monitoring of children with asymptomatic infection at birth and early intervention. Aim: In this multicenter study, we aimed to evaluate the feasibility of using a saliva pool strategy for mass screening in 7 Portuguese hospitals, and to esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A critical consideration with regard to universal screening via sample pooling, refers to the feasibility and logistics and simplicity of operation. A recent study suggested the feasibility of pooling; however, this study included a smaller number of newborn infants (less than half the number of newborn infants screened in the present study), screened over a longer period (2 years), and did not relate to operational considerations 43 . In this study, using our preexistent pooling pipeline, we were able to rapidly incorporate neonatal saliva pooling into routine clinical practice.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A critical consideration with regard to universal screening via sample pooling, refers to the feasibility and logistics and simplicity of operation. A recent study suggested the feasibility of pooling; however, this study included a smaller number of newborn infants (less than half the number of newborn infants screened in the present study), screened over a longer period (2 years), and did not relate to operational considerations 43 . In this study, using our preexistent pooling pipeline, we were able to rapidly incorporate neonatal saliva pooling into routine clinical practice.…”
Section: Discussionmentioning
confidence: 90%
“…In this regard, a few recent proof-of-concept studies suggested the sensitivity of pooling for cCMV testing, yet they included only a few hundred neonates 39 42 . A study in 2023 described the use of pooled saliva testing in 7,033 newborn infants screened for cCMV over a 2-year period 43 . Yet, this study presented limited results, merely describing the feasibility of pooling, with no additional analyses (that is, sensitivity, efficacy and operation).…”
Section: Mainmentioning
confidence: 99%